Bioinformatics : methods and applications - Singh, Dev Bukhsh; Pathak, Rajesh Kumar (Academic Press, 2021)
Systems biology is an emerging field to study the complex interactions in biological systems. The enormous amount of data generated through high-throughput technologies allows the reconstruction of the biological pathways in a structured and dynamic way at the systems level. Hence, for understating the dynamics of these biological pathways, it is necessary to convert the molecular data in the form of biological pathways. Graph theory is utilized for the modeling of complex biological data. Graphs are used to analyze, simulate, and visualize the biological pathways, such as protein-protein interaction and protein metabolite interaction. Motifs are used for the analysis of complex biological networks. The network motifs describe the local properties of a network and are represented as a small connected subgraph, which is frequently appearing in a network. In this chapter, we have described the structure of biological networks, graph theory including its statistical parameters, network motifs, different types of algorithms, and its role in the biological application.